Design and fabrication of electro‐conductive polymer nanocomposites with mechanical and thermal resistance. Issue 9 (13th June 2018) - Batool, Maria; Nadeem, QuratulAin; Gill, Rohama; Nadeem, Raziya
Abstract: The commencement of the industrial revolution paved the way for the fabrication of flexible polymers with high‐strength metalloceramics as novel materials of all kinds. Fabricating metal–ceramic/polymer conductive composites is one such dimension followed for the present research work making use of the properties of the three components. Electroless deposition, for permanent metallic coating, was performed to coat Al2 O3 with metallic Cu followed by the inclusion of the Cu–Al2 O3 filler into a poly(vinyl chloride) (PVC) matrix. X‐ray diffraction and energy‐dispersive X‐ray studies predicted a prominent growth of metallic Cu crystallites onto Al2 O3 with an increased average size and variation in elemental composition, respectively, when compared to pristine Al2 O3 . Morphological behaviour via scanning electron microscopy also envisioned uniform Cu coating onto Al2 O3 and a homogeneous dispersion throughout the polymer matrix. When incorporated into PVC, electrical conductivity analysis highlighted a distinct variation in composite phases from insulating (7.14 × 10 −16 S cm −1 ) to semiconducting behaviour (8.33 × 10 −5 S cm −1 ) as a function of Cu–Al2 O3 filler. Mechanical behaviour (tensile strength, Young's modulus and elongation at break) and thermal properties of the prepared composites also indicated a substantial improvement in material strength with Cu–Al2 O3 incorporation. The enhanced electrical conductivity along with improved thermomechanical status with significant filler–matrix interaction permits the potential usage of such novel composites in a range of state‐of‐the‐art semiconducting electronic devices. © 2018 Society of Chemical Industry Abstract : The fabrication of metal–ceramic/polymer conductive composites is explored.